Thai Youth's First Masturbation: 23-Year Study of Medical Students - Pongthai, Sompol (ANIMA Indonesian Psychological Journal, 2007)
Masturbation is the most favorite sexual outlet of young people. This study aimed to explore the first practice of masturbation as wel as the difference between both sexes on first clinical year medical students More than ninety per cent of both males and females participated. Majority are Buddhist, almost all are not married (N = 2735; 1552 males, & 1173 females) aged 18-37 (with a mean of 21.14 years in males and 20.70 in females) at Ramathibodi Hospital, Mahidol University during the academic year 1982-2004. Data were collected through an anonim questionnaire. Results reveal that 96 % of males and 40% females did masturbation (p < 0.001). Average first starting age is 13.57 yrs old for males and 15.09 for females. First masturbation accounted for 59.25% of male first ejaculation and 77.52% for first female orgasm. The intrinsic as well as especially extrinsic backgrounds of the phenomena are discussed. Masturbasi merupakan penyaluran seksual paling favorit di antara remaja. Studi ini mengeksplorasi awal praktik masturbasi mahasiswa kedokteran tingkat klinis awal Lebih dari 90 % jumlah mahasiswa berperan serta, umumnya beragama Buddha dan hampir semuanya tidak nikah (N = 2735; 1552 pria, & 1173 perempuan) dari Fakultas Kedokteran Universitas Mahidol dari tahun akademik 1982-2004, dengan rentang usia 18-37 tahun (rerata 21.14 pada pria dan 20.70 pada perempuan). Data diperoleh melalui kuesioner anonim. Hasil-hasil menunjukkan 96 % pria dan 40% perempuan melakukan masturbasi (p< 0.001). Rata-rata usia pertama kali masturbasi adalah 13.57 tahun pada pria dan 15.09 tahun pada perempuan. Pengalaman pertama kali menemukan sendiri oleh sejumlah 54.39% pria dan 73.42 % perempuan. Sisanya memperoleh pengetahuan tersebut dari sumber lain. Masturbasi pertama kali dengan ejakulasi dialami oleh 59.25% pria dan orgasme oleh 77.52% perempuan. Didiskusikan latar belakang intrinsik dan terutama ekstrinsik terjadinya fenomena tersebut.